2015
DOI: 10.18632/oncotarget.4022
|View full text |Cite
|
Sign up to set email alerts
|

Mutant AKT1-E17K is oncogenic in lung epithelial cells

Abstract: The hotspot E17K mutation in the pleckstrin homology domain of AKT1 occurs in approximately 0.6-2% of human lung cancers. In this manuscript, we sought to determine whether this AKT1 variant is a bona-fide activating mutation and plays a role in the development of lung cancer. Here we report that in immortalized human bronchial epithelial cells (BEAS-2B cells) mutant AKT1-E17K promotes anchorage-dependent and -independent proliferation, increases the ability to migrate, invade as well as to survive and duplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…First, we observed highly frequent AKT1 gene alterations (somatic mutations and copy gains) in the PSH genomes. Based on the current knowledge of AKT1 mutations (oncogenic activities and recurrent hotspot mutations) (20,27,28), our data suggest that AKT1 gene alterations are the most common genetic driver that might contribute to the PSH development. Recurrent AKT1 mutation was first reported in breast cancers and subsequently in other tumors (29).…”
Section: Discussionmentioning
confidence: 83%
“…First, we observed highly frequent AKT1 gene alterations (somatic mutations and copy gains) in the PSH genomes. Based on the current knowledge of AKT1 mutations (oncogenic activities and recurrent hotspot mutations) (20,27,28), our data suggest that AKT1 gene alterations are the most common genetic driver that might contribute to the PSH development. Recurrent AKT1 mutation was first reported in breast cancers and subsequently in other tumors (29).…”
Section: Discussionmentioning
confidence: 83%
“…41 PIK3CA mutations are detected in 2% of lung carcinomas, 42 and preclinical data suggest a high sensitivity to PI3K inhibitors. 43,44 AKT1 mutations have been observed in 1% of lung adenocarcinomas, 12,45 and targeting AKT1 using microRNAs have shown in vitro and in vivo suppression of lung tumorigenesis. 46 One case of ALK rearranged sarcomatoid carcinoma was identified (3% of total cases), which to our knowledge is quite a rare phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a constitutive membrane localization of the kinase and increased phosphorylation on T308 and S473 in a PI3K-independent manner (Carpten, et al, 2007; Kumar & Purohit, 2013; Landgraf, Pilling, & Falke, 2008). At the functional level, the augmented localization of AKT at the plasma membrane is sufficient to transform cells in vitro and induce leukemia in mice transduced with the human AKT1 E17K allele (Cancer Genome Atlas, 2012; De Marco, et al, 2015). Subsequent analyses of cancer genomes indicated that the AKT1 E17K mutation is present in other tumor types, but is more frequently detected in invasive breast carcinoma with an overall somatic mutation rate of 2.5% (TCGA results from 1098 patients).…”
Section: Akt Alterations In Breast Cancer and Resistance To Anti-erbbmentioning
confidence: 99%